(untitled) (Journal of Business Management and Accounting, 2023)
As natural disaster becomes more common, environmental sustainabilityhasbeguntogainmoreattention. Manyenvironmentalists originating from developed countries have been working towards creating awareness on global warming. Considering the conservation of the environment, the Datai’s target market is the nature lovers from rich and developed countries who are willing to pay more than RM1000 per night for a room. The objective of this case study is to discover the Datai’s sustainability initiatives in its effort to attract customers. Based on a semi-structured interview with the Datai’s Human Resource Director, it is discovered that the luxury resort that is rich in wildlife and faces the Datai Bay invested up to RM 2 million for environmental sustainability. The Datai sustainable environment initiative covers all aspects of life, addressing sustainability issues head on by raising awareness among schoolchildren, the local community, and visitors.